Konsten att kontextualisera: Om historisk förståelse och meningsskapande (Stockholm University Press, 2022)
This book is about the historical sciences' way of producing knowledge by contextualizing. It is aimed primarily at students and researchers in the humanities disciplines who work with historical perspectives. The book's ambition is to bring the reader into the actual making and show how contextualisation is an important element in historical studies at all levels. The book thus hopes to stimulate increased reflection and discussion about how we proceed when we interpret, create or reinterpret historical, cultural and social contexts.The book firstly provides an introduction to what contextualization can be and do when we encounter the past in the form of texts, images or artifacts. From the very first day at the university, students in historical disciplines end up in such meetings. Therefore, the first four chapters of the book are primarily aimed at students in the introductory semesters. What does it really mean to analyze, synthesize, contextualize or criticize - and how do the ways of working with the past relate to each other? And further, what historical times are we working with: do we read source material from our own horizons or from those of the historical actors? Is the source material part of a long story or a short one? And who decides the answer to such questions?Secondly, the book provides an in-depth discussion of the role of contextualisation when we create new historical knowledge. The book's later chapters ask questions about how contextualisation relates to historical theory and method, and sheds light on the activity of creating, arguing for, and reconsidering the contexts that give meaning and significance to historical source material.The most central lesson the book wants to convey is that contextualization is an ongoing activity. Human horizons of understanding are constantly moving in step with contemporary knowledge interests. There will always be new ways of understanding historical expressions, and that is one reason why historical studies form an important part of society's common knowledge base.